2013
DOI: 10.1038/leu.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

The AAA+ ATPase RUVBL2 is a critical mediator of MLL-AF9 oncogenesis

Abstract: The most frequent chromosomal translocations in pediatric acute myeloid leukemia affect the 11q23 locus and give rise to mixed lineage leukemia (MLL) fusion genes, MLL-AF9 being the most prevalent. The MLL-AF9 fusion gene has been shown to induce leukemia in both mouse and human models. In this study, we demonstrate that leukemogenic activity of MLL-AF9 requires RUVBL2 (RuvB-like 2), an AAA þ ATPase family member that functions in a wide range of cellular processes, including chromatin remodeling and transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 45 publications
9
53
0
Order By: Relevance
“…RuvBL proteins belong to the evolutionarily highly conserved AAA+ family (ATPase Associated with various cellular Activities) that are involved in ATP binding and hydrolysis (Matias et al ., ). Eukaryotic RuvBL1 (Pontin, TIP49a, Rvb1, TAP54α) and RuvBL2 (Reptin, TIP48, TIP49b, Rvb2, TAP54β) participate in many diverse cellular activities like chromatin remodeling (Jha et al ., ), transcriptional regulation (Ohdate et al ., ; Gallant, ), oncogenic transformation (Osaki et al ., ), epigenetic regulations (Gallant, ) or DNA‐damage signaling (Rosenbaum et al ., ). RuvBL1 and RuvBL2 can also play a role in the assembly of box C/D or H/ACA of small nucleolar RNAs (snoRNAs) with specific proteins to form functional ribonucleoprotein particles (RNPs) (Watkins et al ., ; McKeegan et al ., ; Boulon et al ., ; Zhao et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…RuvBL proteins belong to the evolutionarily highly conserved AAA+ family (ATPase Associated with various cellular Activities) that are involved in ATP binding and hydrolysis (Matias et al ., ). Eukaryotic RuvBL1 (Pontin, TIP49a, Rvb1, TAP54α) and RuvBL2 (Reptin, TIP48, TIP49b, Rvb2, TAP54β) participate in many diverse cellular activities like chromatin remodeling (Jha et al ., ), transcriptional regulation (Ohdate et al ., ; Gallant, ), oncogenic transformation (Osaki et al ., ), epigenetic regulations (Gallant, ) or DNA‐damage signaling (Rosenbaum et al ., ). RuvBL1 and RuvBL2 can also play a role in the assembly of box C/D or H/ACA of small nucleolar RNAs (snoRNAs) with specific proteins to form functional ribonucleoprotein particles (RNPs) (Watkins et al ., ; McKeegan et al ., ; Boulon et al ., ; Zhao et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, progress has not been uniform across all subtypes of disease and many pediatric 1 and adult 2 Acute Myeloid Leukemia (AML) patients cannot be cured by current therapies. It is widely accepted that further intensification of chemotherapy is unlikely to improve outcomes, 3,4 but that this may be achieved by developing novel therapeutics targeting specific leukemia drug-susceptibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Models of MLLr leukaemia Several MLLr models have been developed to understand the oncogenic mechanisms of the rearrangement. The MLL/AF9 fusion gene has been demonstrated to induce ALL or AML in vitro and in vivo in mice [74,75]. It has been shown that microenvironmental factors impact on lineage commitments of MLL/AF9 acute leukaemia, i.e.…”
Section: 232mentioning
confidence: 99%